Lymphocyte Oxidative Stress/Genotoxic Effects Are Related to Serum IgG and IgA Levels in Coke Oven Workers - Meili Gao; Yongfei Li; Aqun Zheng; Xiaochang Xue; Lan Chen; Yu Kong (The Scientific World Journal)
We investigated oxidative stress/genotoxic effects levels, immunoglobulin levels, polycyclic aromatic hydrocarbons (PAHs) levels exposed in 126 coke oven workers and in 78 control subjects, and evaluated the association between oxidative stress/genotoxic effects levels and immunoglobulin levels. Significant differences were observed in biomarkers, including 1-hydroxypyrene levels, employment time, percentages of alcohol drinkers, MDA, 8-OHdG levels, CTL levels and CTM, MN, CA frequency, and IgG, IgA levels between the control and exposed groups. Slightly higher 1-OHP levels in smoking users were observed. For the dose-response relationship of IgG, IgA, IgM, and IgE by 1-OHP, each one percentage increase in urinary 1-OHP generates a 0.109%, 0.472%, 0.051%, and 0.067% decrease in control group and generates a 0.312%, 0.538%, 0.062%, and 0.071% decrease in exposed group, respectively. Except for age, alcohol and smoking status, IgM, and IgE, a significant correlation in urinary 1-OHP and other biomarkers in the total population was observed. Additionally, a significant negative correlation in genotoxic/oxidative damage biomarkers of MDA, 8-OH-dG, CTL levels, and immunoglobins of IgG and IgA levels, especially in coke oven workers, was found. These data suggest that oxidative stress/DNA damage induced by PAHs may play a role in toxic responses for PAHs in immunological functions.